1986
DOI: 10.1159/000309718
|View full text |Cite
|
Sign up to set email alerts
|

Scintimetric Detection of Choroidal Malignant Melanoma with [<sup>123</sup>I]-5-Iodo-2-Thiouracil

Abstract: [123I]-5-iodo-2-thiouracil (123I-ITU) was evaluated as a radiopharmaceutical for tumor detection in 10 patients with proven choroidal melanoma. Uptake of 123I-ITU was measured with a specially designed single eye probe collimator, 24 h after administration of 123I-ITU. Increased uptake in the tumor-bearing eye as compared to the fellow nontumor bearing eye was found in 7 out of 10 cases when the probe was located 3.5 cm in front of the eye (p < 0.01). By using a doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Also 5-iodo-2-thiouracil (ITU), labeled with radioiodine for possible clinical use, is similarly localized in melanotic melanoma van Langevelde et al, 1983;Coderre et al, 1986;Yamada et al, 1988). Preliminary clinical pilot studies on patients with ocular melanoma (Franken et al, 1986) or disseminated cutaneous melanoma (Olander et al, 1991) have indicated that radioiodinated ITU might be used for gamma scintigraphy scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Also 5-iodo-2-thiouracil (ITU), labeled with radioiodine for possible clinical use, is similarly localized in melanotic melanoma van Langevelde et al, 1983;Coderre et al, 1986;Yamada et al, 1988). Preliminary clinical pilot studies on patients with ocular melanoma (Franken et al, 1986) or disseminated cutaneous melanoma (Olander et al, 1991) have indicated that radioiodinated ITU might be used for gamma scintigraphy scanning.…”
Section: Introductionmentioning
confidence: 99%